2001
DOI: 10.1121/1.1354987
|View full text |Cite
|
Sign up to set email alerts
|

DPOAE group delays versus electrophysiological measures of cochlear delay in normal human ears

Abstract: Group delays of 2 f1-f2 distortion product otoacoustic emissions (DPOAEs) were determined using both f1- and f2-sweep paradigms in 24 normal-hearing subjects. These DPOAE group delays were studied in comparison with cochlear delays estimated from derived band VIIIth nerve compound action potentials (CAPs) and auditory brainstem responses (ABRs) in the same subjects. The center frequencies of the derived bands in the electrophysiological experiment were matched with the f2-frequencies in the DPOAE recording to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 53 publications
4
52
1
Order By: Relevance
“…The latency-frequency functions estimated using otoacoustic emissions or ABR responses become shallower with increasing stimulus level (Neely et al, 1988;Schoonhoven et al, 2001;Sisto and Moleti, 2007). In contrast, Ruggero and Temchin (2007) argued that stimulus level has very little effect on the BM latency-frequency function and the effect is to slightly increase across-frequency latencies at high levels.…”
Section: E Effects Of Levelmentioning
confidence: 87%
See 2 more Smart Citations
“…The latency-frequency functions estimated using otoacoustic emissions or ABR responses become shallower with increasing stimulus level (Neely et al, 1988;Schoonhoven et al, 2001;Sisto and Moleti, 2007). In contrast, Ruggero and Temchin (2007) argued that stimulus level has very little effect on the BM latency-frequency function and the effect is to slightly increase across-frequency latencies at high levels.…”
Section: E Effects Of Levelmentioning
confidence: 87%
“…The exact form of changes in BM latency-frequency function with level is unknown. Some studies have suggested that the latencyfrequency function becomes shallower, exhibiting more synchronous responses across frequency as the level increases (e.g., Neely et al, 1988;Schoonhoven et al, 2001;Sisto and Moleti, 2007), while others have predicted a small effect of level in the opposite direction, i.e., a slight increase in the slope of the latency-frequency function at high levels (Ruggero and Temchin, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, based on the published reports, it is not entirely clear that broader filters are associated with substantial changes to the BM latency-frequency function. Cochlear latency-frequency functions estimated from derivedband ABRs and otoacoustic emissions for different levels of the evoking stimuli have been shown to become shallower with increasing level and thus with increasing filter bandwidths (Neely et al 1988;Schoonhoven et al 2001; Sisto and Moleti 2007).…”
Section: Perceived Across-frequency Synchrony and The Cochlear Latencmentioning
confidence: 99%
“…Of those delays, the build-up times of cochlear-filter responses dominate the frequency-dependent component of the overall delay (Ruggero and Temchin 2007). In humans, the frequency-dependent cochlear delays have been estimated from noninvasive physiological measurements of latencies of the compound action potential (Elberling 1974;Eggermont 1979;Schoonhoven et al 2001), the auditory-brainstem response (ABR; Eggermont and Don 1980;Neely et al 1988;Donaldson and Ruth 1993;Harte et al 2009), and otoacoustic emissions (Neely et al 1988;Bowman et al 1997;Schoonhoven et al 2001;Shera and Guinan 2003;Sisto and Moleti 2007;Harte et al 2009). Generally, the estimated cochlear-response latency in humans has been shown to decrease with increasing CF at a rate similar to that derived from direct physiological measurements in animals.…”
Section: Introductionmentioning
confidence: 99%